Aprotinin may increase mortality in low and intermediate risk but not in high risk cardiac surgical patients compared to tranexamic acid and ε-aminocaproic acid -- a meta-analysis of randomised and observational trials of over 30.000 patients. - Patrick Meybohm (Public Library of Science (PLoS), 2013)
Background To compare the effect of aprotinin with the effect of lysine analogues (tranexamic acid and ε-aminocaproic acid) on early mortality in three subgroups of patients: low, intermediate and high risk of cardiac surgery. Methods and findings We performed a meta-analysis of randomised controlled trials and observational with the following data sources: Medline, Cochrane Library, and reference lists of identified articles. The primary outcome measure was early (in-hospital/30-day) mortality. The secondary outcome measures were any transfusion of packed red blood cells within 24 hours after surgery, any re-operation for bleeding or massive bleeding, and acute renal dysfunction or failure within the selected cited publications, respectively. Out of 328 search results, 31 studies (15 trials and 16 observational studies) included 33,501 patients. Early mortality was significantly increased after aprotinin vs. lysine analogues with a pooled risk ratio (95% CI) of 1.58 (1.13-2.21), p<0.001 in the low (n = 14,297) and in the intermediate risk subgroup (1.42 (1.09-1.84), p<0.001; n = 14,427), respectively. Contrarily, in the subgroup of high risk patients (n = 4,777), the risk for mortality did not differ significantly between aprotinin and lysine analogues (1.03 (0.67-1.58), p = 0.90). Conclusion Aprotinin may be associated with an increased risk of mortality in low and intermediate risk cardiac surgery, but presumably may has no effect on early mortality in a subgroup of high risk cardiac surgery compared to lysine analogues. Thus, decisions to re-license aprotinin in lower risk patients should critically be debated. In contrast, aprotinin might probably be beneficial in high risk cardiac surgery as it reduces risk of transfusion and bleeding complications.